An Examination of Appetite and Disordered Eating in Active Crohn's Disease. (3rd April 2018) - Wardle, Richard Anthony; Thapaliya, Gita; Nowak, Adam; Radford, Shellie; Dalton, Michelle; Finlayson, Graham; Moran, Gordon W
Abstract: Background: Crohn's disease [CD] patients suffer from nutritional deficiencies when in active disease. We aim to examine calorific intake, macronutrient choice, and disordered eating behaviour in patients with active CD. Methods: CD patients with matched healthy volunteers [HV] were recruited. Active disease was defined by faecal calprotectin >250 µg/g, C-reactive protein 83.8 ± 47.1 mg/dL, or active disease seen on endoscopy or imaging. Symptoms were quantified by Harvey‑Bradshaw Index [HBI]. Calorific intake was assessed by 24-h dietary recall. Disordered eating was assessed using validated questionnaires: Binge Eating Scale [BES]; Power of Food Scale [PFS]; Control of Eating Questionnaire [CoEQ]; Dutch Eating Behaviour Questionnaire [DEBQ]; and Three Factor Eating Questionnaire [TFEQ]. Results: Totals of 30 CD (18 male[M]:12 female [F], age 32.3 ± 2.19 years, body mass index [BMI] 24.9 ± 0.8) and 31 matched HV [19 M:12 F, age 32.8 ± 2.0 years, BMI 24.7 ± 0.5] were recruited. Mean faecal calprotectin was 1032.5 ± 176 µg/g, C-reactive protein 8.38 ± 4.71 mg/dL, and HBI 4.8 ± 1. There were no significant differences in calorific intake between groups. Protein intake was lower in the CD cohort [ p = 0.03]. Hospital Anxiety and Depression score was higher [ p = 0.01] and CoEQ-Positive Mood [ p = 0.001] lower in CD. CD patients were characterised by higher BES [ p = 0.01] and lower CoEQ Craving Control [ p = 0.027], with greater craving for Sweet [ p = 0.043] and Savoury [ p = 0.021] foods. PFS food Present [ p = 0.005], DEBQ Emotional [ p =< 0.001], and External Eating [ p = 0.022] were significantly higher than among HV. Conclusions: Reduced protein consumption and more prevalent disordered eating behaviour traits were present in CD. Greater binge eating and decreased control of cravings may be attributed to lower mood and higher anxiety observed. Patients may benefit from stronger psychological support with firm dietetic advice for healthy eating.